Black Soldier Fly Larvae Meal in the Diet of Gilthead Sea Bream: Effect on Chemical and Microbiological Quality of Filets - Oteri, Marianna; Chiofalo, Biagina; Maricchiolo, Giulia; Toscano, Giovanni; Nalbone, Luca; Lo Presti, Vittorio; Di Rosa, Ambra Rita (Frontiers in Nutrition, 2022)
The chemical and microbiological characteristics of filets of Spaurus aurata L. specimens fed with diets containing a Hermetia illucens meal (HIM) at the 25, 35, and 50%, as a partial replacement for fish meal (FM) were evaluated. The diets, formulated to satisfy the nutritional needs of fish, were isoenergetic (22 MJ/kg gross energy), isonitrogenous (43 g/100 g, a.f.), and isolipidic (19 g/100 g, a.f.). Seventy-two specimens were randomly killed after 186 days of growing trials. Then, the filets were analyzed for chemical profile, fatty acids, amino acids, minerals, and microbial flora. Data were subjected to statistical analysis. No significant differences were observed in chemical composition. The sum of polyunsaturated fatty acids (PUFAs) showed a similar content in the filets; eicosapentaenoic acid was similar in the filets of HIM0, HIM35%, and HIM50%, whereas docosahexaenoic acid was higher in filets of the HIM0 group. n3/n6 PUFA ratio and the sum of EPA + DHA showed a high value (p < 0.001) in filets of the group fed with FM. No significant difference was observed in thrombogenic index and hypocholesterolaemic/hypercholesterolaemic ratio in the groups; the atherogenic index showed a higher value (p = 0.001) in the HIM50% group. Indispensable amino acids showed some significant (p < 0.0001) differences in the groups; arginine and phenylalanine content was higher in the filets of fish fed with FM; isoleucine and valine content was higher in the filets of HIM50%; leucine, lysine and methionine content was lower in the filets of HIM35%; histidine content was lower in the filets of HIM25%; tryptophan content was lower in filets of the HIM50% group. EAA/NEAA ratio showed highest value in the filets of the group that received FM. The presence of HIM in the three diets kept chromium, manganese, iron, copper, zinc, and nickel levels lower than those recommended by various authorities. Ca/P ratio showed a higher level (p < 0.0001) in the group fed with FM than those fed with diets containing HIM. The insect meal in the diets did not influence the microbiological profile of fish. Use of HIM as an unconventional feed ingredient in Sparus aurata diet looks promising, although the quality of filets may be affected.